Comparative Study of Angle of Inclination and Neck Length of Dry Femur - Adhikari, Rakesh Kumar; Yadav, Binita; Yadav, Subodh Kumar; Singh, Arun Chandra (Journal of Nobel Medical College, 2017)
Background : The angle of inclination of the femur is the angle formed between long axis of neck of femur and long axis of the shaft of femur. The average angle of inclination (neck–shaft angle) is 126°, ranging from 115° to 140° in the adult population. As with the angle of inclination of the humerus, the angle of inclination of the femur varies among individuals and also from side to side. The aim of this study was to determine the Angle of inclination and neck length of Femur.Material & Methods: A total of 50 dry femora (25right and 25 left) of nobel medical college was cross sectionally studied with random sampling without knowing the sex & age of bone. The angle formed between long axis of neck and long axis of the shaft of femur was measured with the help of goniometer. The neck length was measured with the help of sliding calliper.Results: The mean angle of inclination was 128.98±4.55 degrees, on the right side was129.84±5.22 degrees and on the left side was 128.12±3.66degrees. The difference in the mean angle of inclination of right and the left side was found to be statistically insignificant (p value> 0.05). The mean neck length femur was 2.93 ±0.24cm, right femur was 3.06±0.19cm and left femur was 2.80±0.21cm. The difference in the mean neck neck length of the right and the left side was found to be statistically insignificant (p value> 0.05).Conclusion: The Angle of Inclination of Femur and neck length of femur in present study had no remarkable dissimilarity with the results observed in the studies conducted in Nepal and neighbouring countries. In the study there was no statistical significant difference between the neck-shaft angle and neck length of femur of right and left side of the femur but there was positive correlation between angle of inclination and neck length of femur.Journal of Nobel Medical CollegeVolume 6, Number 1, Issue 10 (January-June, 2017), Page: 44-47